PERAN LAYANAN BIMBINGAN DAN KONSELING DALAM MENINGKATKAN PENYESUAIAN DIRI INDIVIDU POPULASI KHUSUS - Wan Hanis Masfufah Al; Tasya Putri Cahaya; Gusman Lesmana (Kampus Akademik Publiser, 2026)
This study is motivated by the increasing need for guidance and counseling services for special populations, such as individuals with disabilities, victims of violence, at-risk adolescents, prisoners, and problematic migrant workers who face difficulties in the process of self-adjustment. The main problem addressed in this study is how guidance and counseling services contribute to improving the psychological and social adaptation abilities of these vulnerable groups. The objective of this study is to analyze the effectiveness of guidance and counseling services, the intervention models applied, and their implications for the self-adjustment of special populations. This research employed a library research method using a descriptive qualitative approach through thematic synthesis of various empirical studies and related scientific literature. The findings indicate that guidance and counseling services significantly contribute to improving self-efficacy, adaptive coping skills, self-awareness, and social support among clients. REBT-based counseling, feminist counseling, family counseling, and trauma-informed approaches were found to be effective in specific contexts. The novelty of this study lies in its integrated synthesis across various special populations regarding the effectiveness of guidance and counseling services on self-adjustment. This study contributes as a foundation for developing more inclusive, contextual, and needs-based guidance and counseling services for vulnerable groups, although it is limited to literature-based analysis without primary data